2016
DOI: 10.13031/jash.22.11709
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Track Agricultural Tractors: A Survey on the Load of the Hand-Operated Foldable Rollbar

Abstract: To protect the driver in case of a tractor overturn, narrow-track tractors (used in vineyards and orchards) can be equipped with a rollover protective structure (ROPS) consisting of a two-pillar front-mounted foldable rollbar. The transition from the horizontal (rest) to the vertical (protection) position of this ROPS is performed manually by the driver. In addition to the time spent performing this task many times each day, a moderate physical load is required, given that these rollbars often have a mass of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Other studies dealt with the analysis of the actuation forces needed to operate foldable rollover protective structures (FROPSs) [97,98], whereas Pessina et al [99] compared the handling load of different narrow-track tractors' FROPSs with the related grasping area. Furthermore, two studies describing field tests aimed at setting a warning device based on the operative conditions of the tractor [100,101] were included in this research stream.…”
Section: Ergonomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies dealt with the analysis of the actuation forces needed to operate foldable rollover protective structures (FROPSs) [97,98], whereas Pessina et al [99] compared the handling load of different narrow-track tractors' FROPSs with the related grasping area. Furthermore, two studies describing field tests aimed at setting a warning device based on the operative conditions of the tractor [100,101] were included in this research stream.…”
Section: Ergonomicsmentioning
confidence: 99%
“…The latter issue was stressed by different studies, shedding light on the necessity of updating technical standards such as the OECD Codes, taking into account the features of modern tractors (e.g., the tractor ballast [120]) and how they are used in practice [65,118]. Similarly, the lack of a clear reference for dynamic tests of ROPS was outlined [117,126], while the inadequacy of the standards related to FROPSs testing (e.g., concerning the grasping area [99] and the actuation torque [97]) needs to be further investigated.…”
mentioning
confidence: 99%
“…On the other hand, other investigations [28,29] concluded that there is a strong need to increase the skill of the non-professional tractor drivers, above all what concerns the risk of overturning. Unfortunately, the characteristics of the investigation of the present survey (i.e., the level of information obtained) did not allow the classification of the victims between professional and non-professional (retired and part-time) workers.…”
Section: Discussionmentioning
confidence: 99%
“…There is, thus, some uncertainty in knowing how the rollover energy is partitioned to the ROPS and other components during contemporary, real rollover events corresponding to common modern tractor configurations. In addition, a recent issue that has arisen at the international level refers to the adoption of foldable ROPSs and their incorrect use among users responsible for the relevant percentage of the fatal accident occurring with tractors [ 20 , 21 , 22 , 23 , 24 , 25 ]. Hence, although the pioneering works are fundamental to the establishment of the standards, the applicability of the resulting standardized procedure to today’s diverse tractor fleet and configurations is somewhat unknown.…”
Section: Introductionmentioning
confidence: 99%